Increased RNAi Efficacy in Spodoptera exigua via the Formulation of dsRNA With Guanylated Polymers - Christiaens, Olivier; Tardajos, Myriam G.; Martinez Reyna, Zarel L.; Dash, Mamoni; Dubruel, Peter; Smagghe, Guy (Frontiers in Physiology, 2018)
Lepidoptera comprise some of the most devastating herbivorous pest insects worldwide. One of the most promising novel pest control strategies is exploiting the RNA interference (RNAi) mechanism to target essential genes for knockdown and incite toxic effects in the target species without harming other organisms in the ecosystem. However, many insects are refractory to oral RNAi, often due to rapid degradation of ingested dsRNA in their digestive system. This is the case for many lepidopteran insects, including the beet armyworm Spodoptera exigua, which is characterized by a very alkaline gut environment (pH>9.0) and a strong intestinal nucleolytic activity. In this research, guanidine-containing polymers were developed to protect dsRNA against nucleolytic degradation, specifically in high pH environments. First, their ability to protect dsRNA against nucleolytic degradation in gut juice of the beet armyworm S. exigua was investigated ex vivo. Polymers with high guanidine content provided a strong protection against nucleolytic degradation at pH 11, protecting the dsRNA for up to 30 hours. Next, cellular uptake of the dsRNA and the polyplexes in lepidopteran CF203 midgut cells was investigated by confocal microscopy, showing that the polymer also enhanced cellular uptake of the dsRNA. Finally, in vivo feeding RNAi bioassays demonstrated that using these guanidine-containing polymer nanoparticles led to an increased RNAi efficiency in S. exigua. Targeting the essential gene chitin synthase B, we observed that the mortality increased to 53% in the polymer-protected dsRNA treatment compared to only 16% with the naked dsRNA and found that polymer-protected dsRNA completely halted the development of the caterpillars. These results show that using guanylated polymers as a formulation strategy can prevent degradation of dsRNA in the alkaline and strongly nucleolytic gut of lepidopteran insects. Furthermore, the polymer also enhances cellular uptake in lepidopteran midgut cells. This new delivery strategy could be of great use in further fundamental research in lepidopterans, using RNAi as a research tool, and could lead to future applications for RNAi-based pest control of lepidopteran insects.